Hydrogen evolution by a low cost photocatalyst: bauxite residue - Mangrulkar, Priti A.; Joshi, Meenal V.; Kamble, Sanjay P.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
Bauxite residue or red mud which is an aluminium industry waste has been used as a novel low cost photocatalyst active in visible light for the generation of hydrogen from water. The driving force behind the use of bauxite residue as a photocatalyst is not only the fact that it is widely available but also bauxite residue is a fine grained mixture of oxides and hydroxides (Fe(2)O(3), TiO(2), SiO(2), and Al(2)O(3), Al(OH)3). The photocatalyst was characterized with respect to BET-SA, UV-DRS, XRD, SEM and EDX. Hydrogen yield of 4600 mu mol/h/g of TiO(2) was achieved as compared to hydrogen evolution rate of 164 mu mol/h/g of TiO(2) for commercially available titania Degussa P-25. However, the hydrogen evolution was 20.85 mu mol/h/g of photocatalyst. The results suggest that bauxite residue appears to be a novel low cost photocatalyst. The various operating conditions of photocatalytic hydrogen generation were studied which include amount of catalyst, illumination intensity, illumination time, effect of various sacrificial donors etc. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Aluminium industry waste; Bauxite residue; Hydrogen generation; Red mud; Sacrificial donors

High throughput sequencing based direct detection of SARS-CoV-2 fragments in wastewater of Pune, West India - Dharmadhikari, Tanmay; Rajput, Vinay; Yadav, Rakeshkumar; Boargaonkar, Radhika; Patil, Dhawal; Kale, Saurabh; Kamble, Sanjay P.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2022)
Given a large number of SARS-CoV-2 infected individuals, clinical detection has proved challenging. The wastewater-based epidemiological paradigm would cover the clinically escaped asymptomatic individuals owing to the faecal shedding of the virus. We hypothesised using wastewater as a valuable resource for analysing SARS-CoV-2 mutations circulating in the wastewater of Pune region (Maharashtra; India), one of the most affected during the covid-19 pandemic. We conducted study in open wastewater drains from December 2020- March 2021 to assess the presence of SARS-CoV-2 nucleic acid and further detect mutations using ARTIC protocol of MinION sequencing. The analysis revealed 108 mutations across six samples categorised into 39 types of mutations. We report the occurrence of mutations associated with Delta variant lineage in March-2021 samples, simultaneously also reported as a Variant of Concern (VoC) responsible for the rapid increase in infections. The study also revealed four mutations; S:N801, S:C480R, NSP14:C279F and NSP3:L550del not currently reported from wastewater or clinical data in India but reported worldwide. Further, a novel mutation NSP13:G206F mapping to NSP13 region was observed from wastewater. Notably, S:P1140del mutation was detected in December 2020 samples while it was reported in February 2021 from clinical data, indicating the instrumentality of wastewater data in early detection. This is the first study in India to demonstrate utility of sequencing in wastewater based epidemiology to identify mutations associated with SARS-CoV-2 virus fragments from wastewater as an early warning indicator system. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: ARTIC protocol; Epidemiology; Metagenomics; Nanopore sequencing; SARS-CoV-2; wastewater

Highly efficient chemoselective hydrogenation of 5-HMF to BHMF over reusable bimetallic Pd-Ir/C catalyst - Ratrey, Geetanjali; Solanki, Bhanupratap S.; Kamble, Sanjay P.; Rode, V. Chandrashekhar (ChemistrySelect, 2022)
Catalytic synergism was observed for a bimetallic Pd-Ir catalyst supported on activated carbon for chemoselective hydrogenation of 5-hydroxymetahyl furfural (5-HMF) to 2, 5-(bishydroxymethyl) furan (BHMF) with complete conversion and 97 % selectivity under very mild reaction conditions. The structural characterization like XRD, N-2 sorption, FE-SEM and TEM suggested formation of fine nanoparticles (1.95-3.08 nm) having very higher surface area, uniform distribution and mesoporous nature of the material. XPS spectra and Pyridine-IR spectroscopy revealed formation of Pd-PdO and Ir/IrO2/IrO3 interface on the catalytic surface along with strong Bronsted acidic sites which were responsible for high efficiency of catalyst at 80 degrees C, 100 psig H-2 pressure at 5-HMF/Catalyst=20 and within 2.5 h of reaction time. A plausible reaction mechanism is also elucidated based on structure activity correlation.
Keywords: 5-HMF; Carbon; Catalytic synergism; Selective hydrogenation; Valorization

Hydrodechlorination of 4-chloro-2-aminophenol into a recyclable product using Ni- and Cu-based catalysts - Shetty, Rohit R.; Raut, Sandesh S.; Kulkarni, Prashant S.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2022)
The 4-chloro-2-amino phenol (4C2AP) bearing wastewater is produced while manufacturing dyes and pharma-ceutical ingredients. Ni-and Cu-based cost-effective catalysts were developed, typically characterized, and subjected to hydrodechlori-nation (HDC) of 4C2AP. The role of reducing agents, concentration, pH of wastewater, presence of salt, reaction temperature, catalyst reuse, and the kinetics was investigated. A selective makeover of 2-amino phenol (2AP) was analyzed by HPLC, LCMS, and NMR. A complete HDC of 4C2AP with remarkable selectivity (98%) toward 2AP was achieved using a Ni0 catalyst and NaBH4 at room temperature. It is observed that the alkaline condition, the presence of salt, and a high reaction temperature favor the HDC process. A maximum of 1 g L-1 of the Ni0 loading is found to be sufficient to dechlorinate the pollutant. It can be concluded that the catalytic HDC is a technically viable and inexpensive process for the conversion of 4C2AP into a valuable product, 2AP.